OPTIMALISASI KEUNTUNGAN PADA PRODUKSI TEMPE DENGAN PENERAPAN LINEAR PROGAMMING DI KECAMATAN BANJAR KOTA BANJAR JAWA BARAT - Jatmiko, Dhanar Dwi Hary; Oktavianingtyas, Ervin; Isnasari, Suci (Department of Mathematics Education , University of Jember, 2021)
Soybean is one of the main food commodities after rice and corn. Tempe is a traditional food made from soybeans. Tempe is widely produced by small and medium industries. This study aims to determine the maximum benefits obtained in the District of Banjar, Banjar City, West Java Province in producing tempe. This type of research is a descriptive study with a qualitative approach. By using the probably sampling method, take a random sample. Determination of the sample is taken in 3 tempe productions with different tempe production income. By determining the decision variables, objective functions, and constraint functions by linear programming methods. In Tempe production in the Banjar District, Banjar City, West Java, the maximum profit was Rp. 29.257.080 and the maximum income was Rp. 28.862.790. The maximum profit and income are obtained from a large workforce so that it can produce a lot of tempe production and the cost of depreciation of the tool is small. The more tempe production, the more revenue obtained.